1996
DOI: 10.1046/j.1365-2443.1996.d01-253.x
|View full text |Cite
|
Sign up to set email alerts
|

The directionality of RuvAB‐mediated branch migration: in vitro studies with three‐armed junctions

Abstract: Background: The Escherichia coli RuvA and RuvB proteins promote the branch migration of 4-way (Holliday) junctions during genetic recombination. The active complex is a tripartite structure in which RuvA protein is bound to the crossover and is sandwiched between two hexameric rings of RuvB. Branch migration requires ATP hydrolysis and occurs as the DNA passes through each RuvB ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In contrast, DNA helicase activity and branch migration of three-way junctions appeared unaffected. Branch migration of Y-junctions is driven by a single RuvB hexamer (39). The defined polarity of the DNA helicase activity (50) also implies the involvement of a single RuvB hexamer in this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, DNA helicase activity and branch migration of three-way junctions appeared unaffected. Branch migration of Y-junctions is driven by a single RuvB hexamer (39). The defined polarity of the DNA helicase activity (50) also implies the involvement of a single RuvB hexamer in this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…A tetramer of RuvA binds Holliday junction DNA and loads two hexameric RuvB helicase rings on opposite arms of the junction (13). The RuvB hexamers pull opposing duplex arms of the junction through the rings with the result being active movement of the branch point along the DNA as it spools across the face of the RuvA tetramer (14,15). The third component of this complex, a dimer of RuvC, binds to the branch point on the opposite face of the Holliday junction to RuvA and cleaves the junction symmetrically when specific sequences are present at the branch point (16 -19).…”
mentioning
confidence: 99%
“…Electron microscopic visualization of the RuvAB-Holliday junction complex revealed that the junction lies sandwiched between two RuvA tetramers and that branch migration is driven by two oppositely oriented RuvB rings that bind to opposing arms (Parsons et al 1995;Yu et al 1997). During branch migration, the DNA passes through RuvA and exits the complex through the cavity in each RuvB ring (Hiom et al 1996).…”
mentioning
confidence: 99%